Baik Dan Buruk Animasi : Refleksi Gaya Komunikasi Mahasiswa KPI Banda Aceh - Agmeliani, Cut Chusnul; Nurdin, Hanifah; Sari, Fitri Meliya (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Animation is a highly popular entertainment medium among university students, yet not all animated content conveys positive values. Animations contain harsh language and messages that contradict Islamic communication ethics, creating a tension between the identity of Islamic Communication and Broadcasting (KPI) students as future da'i/da'iah and their daily communication practices influenced by inappropriate media content. This study examines how both positive and negative animations shape the communication style of KPI students at UIN Ar-Raniry Banda Aceh. Guided by cultivation theory, symbolic interactionism, and uses and gratifications, the research explores how messages are internalized, meanings are negotiated, and motivations drive media consumption. Using a qualitative descriptive-analytical method, data were collected through observation, interviews, and documentation via purposive sampling. Findings show that students’ preferences for animation are driven by motivation, graphic quality, contextual narratives, engaging plots, entertainment value, and learning elements. Animation generates dual influences on communication style: positive impacts include creativity, proper language use, moral internalization, improved communication quality, and critical thinking; while negative effects involve harsh intonation, inappropriate vocabulary, and non-contextual mimicry. This study highlights the need for reflective media consumption and contributes novelty through a comprehensive comparison of positive and negative animations integrated with Islamic communication principles (qaulan ma’rufa).